2017
DOI: 10.1084/jem.20162011
|View full text |Cite
|
Sign up to set email alerts
|

Microglial complement receptor 3 regulates brain Aβ levels through secreted proteolytic activity

Abstract: Czirr et al. report that microglia lacking complement receptor 3 display increased extracellular Aβ degrading activity and that targeting the receptor with a small molecule increases Aβ clearance in vivo, thus identifying a microglial receptor as a novel therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 68 publications
5
80
1
Order By: Relevance
“…Increasing evidence suggested that activated microglia is a key causative factor in in ammation-mediated neurodegeneration and behavior de cits [42]. Dys-regulated microglial activation is reported to be able to increase pathological protein aggregation and impair synaptic pruning and neuron plasticity in key brain regions sub-serving cognition [43,44]. In the present study, activated microglia were detected in the hippocampus and cortex of rotenone-induced mouse PD model.…”
Section: Discussionsupporting
confidence: 55%
“…Increasing evidence suggested that activated microglia is a key causative factor in in ammation-mediated neurodegeneration and behavior de cits [42]. Dys-regulated microglial activation is reported to be able to increase pathological protein aggregation and impair synaptic pruning and neuron plasticity in key brain regions sub-serving cognition [43,44]. In the present study, activated microglia were detected in the hippocampus and cortex of rotenone-induced mouse PD model.…”
Section: Discussionsupporting
confidence: 55%
“…*Note that CD59 is an inhibitor of complement pathway activity, so the synapse/neuron loss seen with CD59 knockout is consistent with a beneficial effect of reducing complement activation. Reference (Ref) 1, Fonseca et al, 2004 ; Ref 2, Hong et al, 2016 ; Ref 3, Fonseca et al, 2017 ; Ref 4, Shi et al, 2015 ; Ref 5, Shi et al, 2017a ; Ref 6, Maier et al, 2008 ; Ref 7, Wyss-Coray et al, 2002 ; Ref 8, Czirr et al, 2017 ; Ref 9, Fonseca et al, 2009 ; Ref 10, Olmos-Alonso et al, 2016 ; Ref 11, Spangenberg et al, 2016 ; Ref 12, Britschgi et al, 2012 ; and Ref 13, Asai et al, 2015 . FB (FD, FH, FI), complement factor B (D, H, I); KO, knockout; MASP, MBL-associated serine protease; MBL, mannose-binding lectin.…”
Section: Detrimental Activities Of Microglia In Admentioning
confidence: 99%
“…Fu and colleagues have shown that APP/PS1 mice treated with the cytokine IL-33 present lower levels of pro-inflammatory gene expression (i.e., IL-1β , IL-6 , NLRP3 ) in association with reduced Aβ load, increased magnitude of long-term potentiation (LTP) at Schaffer collateral-CA1 synapses, and improved cognitive function [ 99 ]. Blockage of mediators of the complement cascade, including C1q [ 100 ], C3 [ 101 , 102 ], and C5a [ 103 ], also confers neuroprotective effects in mouse models of AD. Moreover, deficiency of IκB kinase β, which activates NF-κB, in microglia reduces inflammatory activation and Aβ load in the brain of TgCRND8-APP mice, effects which are associated with a reduction in cognitive deficits and preservation of synaptic structural proteins [ 104 ].…”
Section: The Complexity Of Pro- and Anti-inflammatory Timingmentioning
confidence: 99%